Establishment of a pulmonary epithelial barrier on biodegradable poly-L-lactic-acid membranes. - Salvatore Montesanto; Natalie P Smithers; Fabio Bucchieri; Valerio Brucato; Vincenzo La Carrubba; Donna E Davies; Franco Conforti (PLoS ONE, 2019)
Development of biocompatible and functional scaffolds for tissue engineering is a major challenge, especially for development of polarised epithelia that are critical structures in tissue homeostasis. Different in vitro models of the lung epithelial barrier have been characterized using non-degradable polyethylene terephthalate membranes which limits their uses for tissue engineering. Although poly-L-lactic acid (PLLA) membranes are biodegradable, those prepared via conventional Diffusion Induced Phase Separation (DIPS) lack open-porous geometry and show limited permeability compromising their use for epithelial barrier studies. Here we used PLLA membranes prepared via a modification of the standard DIPS protocol to control the membrane surface morphology and permeability. These were bonded to cell culture inserts for use in barrier function studies. Pulmonary epithelial cells (H441) readily attached to the PLLA membranes and formed a confluent cell layer within two days. This was accompanied by a significant increase in trans-epithelial electrical resistance and correlated with the formation of tight junctions and vectorial cytokine secretion in response to TNFα. Our data suggest that a structurally polarized and functional epithelial barrier can be established on PLLA membranes produced via a non-standard DIPS protocol. Therefore, PLLA membranes have potential utility in lung tissue engineering applications requiring bio-absorbable membranes.